HPLC quantification of seven quaternary benzo[c]phenanthridine alkaloids in six species of the family Papaveraceae - Gregorová, Jana; Bochořáková, Hana; Paulová, Hana; Musil, Pavel; Táborská, Eva (Journal of pharmaceutical and biomedical analysis, 2007)
The content of the seven quaternary benzo[c]phenanthridine alkaloids (QBA) sanguinarine (SA), chelerythrine (CHE), chelirubine (CHR), chelilutine (CHL), sanguilutine (SL), sanguirubine (SR) and macarpine (MA) was determined in the underground part of six plant species of the family Papaveraceae (Sanguinaria canadensis L., Dicranostigma lactucoides HOOK.f.et THOMS, Chelidonium majus L., Macleaya cordata (Willd.), Macleaya microcarpa (Maxim) and Stylophorum lasiocarpum (Oliv.)). HPLC method with reversed phase column Synergi Max-RP C-12 Phenomenex was used, mobile phase consisted of heptanesulfonic acid (0.01 mol/l) with triethanolamine (0.1 mol/l) in redistilled water, pH 2.5, acetonitrile gradient 25-60% during 25 min. Detection was performed at 280 nm. The highest content of SA and CHE was found in the roots of D. lactucoides (1.99%, resp. 3.43% of the dried roots). In rhizomes of S. canadensis was their content more then two times lower.
Keywords: financování organizované; methanol; Regression Analysis; Phenanthridines; acetonitrily; Hydrogen-Ion Concentration; rostlinné extrakty; druhová specificita; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; Molecular Structure; alkaloidy; Calibration; Methanol; Species Specificity; Papaveraceae; spektrofotometrie ultrafialová; regresní analýza; voda; Financing, Organized; léčivé rostliny; molekulární struktura; kalibrace; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; Water; ethanolaminy; Acetonitriles; Alkaloids; Plant Roots; Spectrophotometry, Ultraviolet; Plant Extracts; Ethanolamines; fenantridiny; Plants, Medicinal; kořeny rostlin; koncentrace vodíkových iontů